2011
DOI: 10.1007/s00709-011-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of loop-mediated isothermal amplification (LAMP)-based technology for authentication of Catharanthus roseus (L.) G. Don

Abstract: In this study, loop-mediated isothermal amplification (LAMP)-based molecular marker was developed for authentication of Catharanthus roseus, a medicinal plant. Samples of this plant were collected from different geographical locations in India. Random amplified polymorphic deoxyribonucleic acid (DNA) analysis of collected samples was carried out with 25 random primers. A 610-bp DNA fragment, common to all accessions, was eluted, cloned, and sequenced. Four LAMP primers were designed on the basis of sequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Because of its sensitivity, specificity, efficiency, rapidity, and simplicity, the LAMP method is an ideal molecular technique for identifying certain infectious diseases 16 17 and conducting food hygiene quality control 18 19 , inspection, and quarantine 20 21 . A number of reports have demonstrated that LAMP may be useful for the detection of some plants and medicinal herbs 22 23 24 25 ; however, a standard operating procedure (SOP) for on-site molecular authentication of Chinese herbs has not yet been established. DNA barcoding is currently an effective and widely used tool that enables the accurate identification of plant species.…”
mentioning
confidence: 99%
“…Because of its sensitivity, specificity, efficiency, rapidity, and simplicity, the LAMP method is an ideal molecular technique for identifying certain infectious diseases 16 17 and conducting food hygiene quality control 18 19 , inspection, and quarantine 20 21 . A number of reports have demonstrated that LAMP may be useful for the detection of some plants and medicinal herbs 22 23 24 25 ; however, a standard operating procedure (SOP) for on-site molecular authentication of Chinese herbs has not yet been established. DNA barcoding is currently an effective and widely used tool that enables the accurate identification of plant species.…”
mentioning
confidence: 99%
“…In light of the critical requirement for convenient ingredient and contamination detection, a rapid fluorescent method for the identification of medicinal species is highly desirable. Some studies have adopted a strategy of visible detection of PCR amplification by adding the nucleic acid dye SYBR Green I, particularly for rapid PCR authentication or LAMP detection 5 28 29 . However, primer dimers also generate fluorescence because of the intercalation of nonspecific dye in double-stranded DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Similar method was also devoted to the identification of traditional Chinese medicine Cordyceps sinensis (dong chong xia cao) and its adulterants C. hawresii, C. ramosa, C. liangschanensis, C. militaris, and C. barnesi (Li K. et al, 2011). In another study, LAMP can be combined with RAPD amplification to identify Catharanthus roseus (Chaudhary et al, 2012). These studies demonstrated that LAMP facilitates not only identification but also screening with high specificity.…”
Section: Overview Of Lamp Analysis Methods In Herbal Medicine Identifmentioning
confidence: 96%